2019
DOI: 10.1016/j.yclnex.2019.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Macronutrient composition in human milk from mothers of preterm and term neonates is highly variable during the lactation period

Abstract: Objective: To investigate the macronutrient content of human milk during the first 28 days of lactation of mothers who delivered preterm infants, and to compare preterm to term milk. Methods: A prospective and longitudinal study of mothers at various stages of lactation was conducted in the Amiens-Picardie University Hospital (France). Fat, true protein, carbohydrate and energy contents were estimated in human milk collected from each participant. Results: Macronutrients in human milk were: fat (g/100 mL), 3.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 56 publications
0
13
0
2
Order By: Relevance
“…Ferreira et al also reported that different HMOs contributed to the HMO profile based on parity using non-negative matrix factorization [ 16 ]. As parity is associated with maternal BMI [ 58 , 59 ] and increased interpregnancy BMI with every additional delivery [ 58 ], the relationship between maternal BMI and human milk fatty acid composition [ 60 ] and fat and protein concentration [ 61 ] indicate that it is possible that parity may impact HMO content. Furthermore, shorter and longer interpregnancy intervals have been shown to influence maternal body composition and breastfeeding practices [ 62 ], which may impact HM composition, including HMOs.…”
Section: Discussionmentioning
confidence: 99%
“…Ferreira et al also reported that different HMOs contributed to the HMO profile based on parity using non-negative matrix factorization [ 16 ]. As parity is associated with maternal BMI [ 58 , 59 ] and increased interpregnancy BMI with every additional delivery [ 58 ], the relationship between maternal BMI and human milk fatty acid composition [ 60 ] and fat and protein concentration [ 61 ] indicate that it is possible that parity may impact HMO content. Furthermore, shorter and longer interpregnancy intervals have been shown to influence maternal body composition and breastfeeding practices [ 62 ], which may impact HM composition, including HMOs.…”
Section: Discussionmentioning
confidence: 99%
“…HM is a dynamic and bioactive fluid that varies between mothers. Furthermore, its composition varies according to the lactation stage and between preterm and term breast milk [16,17]. The first form of milk produced in the early days after birth is colostrum.…”
Section: Variation In Human Milk Composition According To the Lactation Stagementioning
confidence: 99%
“…Nota-se m/z 874 é o pico mais intenso nos pools de colostro e de leite de transição com predominância de P; o precursor Ln e o AGPI-CL Ep também podem compor as combinações, sendo este último importante constituinte do cérebro e retina do neonato (Shahi et al, 2019). Além disso, Ep desempenha papel importante na resposta inflamatória e imune, por ser considerado anti-inflamatório (Léké et al, 2019).…”
Section: Espectrometria De Massas Com Ionização Electrospray (Esi-ms)unclassified